Creep behavior modeling of silica fume containing Al2O3–MgO refractory castables - Tomba Martinez, Analia Gladys (2011)
Alumina–magnesia refractory castables usually present silica fume in their compositions, due to their ability to induce better flowability and to compensate the expansion related to the in situ spinel formation. In this paper, four compositions containing distinct silica fume content (0–1 wt%) were designed and analyzed by creep resistance and hot mechanical strength. The u-projection concept coupled with the thermodynamic simulations were used in order to predict the creep behavior and to identify the main mechanism leading to the deformation of the samples. Based on the collected results, a linear correlation between the creep parameters (ui) and the silica fume content was attained by analyzing the experimental data, resulting in reliable data and the likelihood to simulate the performance of other compositions in the same system. Moreover, particle sliding assisted by viscous flow was suggested as the dominant creep mechanism in the studied castables.